Frequency of Hepatitis B Virus and Hepatitis C Virus Infection in Beta Thalassemia Major Children in Tertiary Care Hospital - Altaf, Warisha; Hussain, Maqbool (Indus Journal of Bioscience Research, 2025)
Introduction: The study aimed to determine the frequency of hepatitis B virus and hepatitis C virus infection in children with beta thalassemia major receiving treatment at a tertiary care hospital. Methodology: This descriptive cross-sectional study was conducted over six months, from April 2024 to October 2024, in the Department of Pediatrics at PIMS Hospital, Islamabad. A total of 161 beta-thalassemia major patients, aged 1 to 15 years, were included using non-probability consecutive sampling. Participants with prior HBV or HCV diagnoses, liver disease, or a history of antiviral treatment were excluded. Data on demographics, transfusion history, and infection status were collected. Blood samples were analyzed for HBV and HCV RNA levels using Real-Time PCR. Statistical analysis was performed using SPSS version 26, with infections stratified by age, gender, and transfusion frequency. A p-value ≤0.05 was considered statistically significant. Results: The mean age of participants was 7.98±4.29 years, with an average of 15.95±8.57 transfusions. Males constituted 59.6% of the sample. HBV was detected in 9.9% of patients, and HCV in 31.7%. HBV positivity was significantly associated with age (>10 years: 17%, p=0.036) and number of transfusions (>20 transfusions: 17%, p=0.036). Similarly, HCV positivity dramatically increased with age (>10 years: 83%, p=0.000) and transfusions (>20 transfusions: 83%, p=0.000). Gender differences in infection rates were not statistically significant. Conclusion: Hepatitis B and C infections pose significant risks for beta-thalassemia major patients, with HCV showing a higher prevalence. Older age and increased transfusions significantly elevate infection risk, underscoring the need for enhanced screening protocols and targeted preventive strategies.